Experimental assessment of Neo-Assyrian bronze arrowhead penetration: An initial study comparing bilobate versus trilobate morphologies. (February 2021) - Mullen, Damon; Matney, Timothy; Morrison, Alex; Fisch, Michael; Buchanan, Briggs; Bebber, Michelle R.
Highlights: Neo-Assyrian soldiers used multiple arrowhead styles in their weapons arsenal. Here, we assessed the comparative efficiency of bilobate and trilobate arrowheads. This initial study focused on arrowhead penetration ability. Our results show that morphology plays a role in arrowhead penetration depth. Abstract: Archaeological evidence shows that Neo-Assyrian soldiers used multiple arrowhead styles in their weapons arsenal. Indeed, finds from the site of Ziyaret Tepe, located in southeastern Turkey, show that both bilobate and trilobate arrowheads were found in association. Of interest to this study are the factors promoting the invention and perseverance of the trilobate arrowhead form. Manufacturing a trilobate point would have been more costly in both raw materials and energy needed to cast a complex three-dimensional form compared its bilobate counterpart. When considered from an economic standpoint, this generates questions regarding the factors that may have promoted the use of the more complex trilobate arrowheads. To better understand the development of trilobate forms, we began a series of experiments designed to assess the comparative functional efficiency of socketed bilobate versus the socketed trilobate arrowheads made from bronze. This initial study is the first in a long-term experimental program designed to understand variation in performance between arrowhead types. This foundational study focuses on an isolated variable—arrowhead penetration depth— in order to establish a baseline parameter for designing future studies in this series. Our results show that morphology does play a role in arrowhead performance, with bilobate forms penetrating significantly deeper into the target material, however, these results do not explain the functional benefit of the trilobate morphology.